Melt Derived Fabrication Of Bioactive Glass And Biocompatibility Evaluation Towards Dental Pulp Stem Cell - Zain, Nurul Shazwani Mohd (2018)
Bioactive glass (BG) has the ability to bond to hard and soft tissues, and promotes bone growth. BG 45S5, with composition of 46.1% SiO2, 26.9% CaO, 24.4% Na2O, and 2.5% P2O5 in mole percentages (mol.%), and a new composition (BG 44S), with similar network connectivity were fabricated via melt derived route using similar melting temperature and soaking time. The 44S composition was proposed to decrease melting temperature during fabrication. The BG preparations included batching, mixing, melting at 1400 °C, water quenching, milling, and sieving. BG 45S5 possessed lower average particle size (11.8 μm) based on the particle size analysis. Both BG were in amorphous phase based on X-Ray Diffraction (XRD) analyses and contained mainly silicate network, with Si-O-Si functional groups, using Fourier Transform Infrared spectroscopy. Both BG were subjected to simulated body fluid incubation to assess the bioactivity for hydroxyl carbonate apatite (HCA) layer formation, followed by characterisations. Functional groups of P-O and C-O bonds, which attributed to HCA layer formation were present at day 1 for BG 44S, and at day 7 for BG 45S5. The hydroxyapatite (HA) layer started to develop on both BG surfaces at day 1, followed by formation of HCA cluster crystal at day 21 based on Scanning Electron Microscope (SEM) images and Energy Dispersive X-ray Spectroscopy (EDX) analyses upon immersion in SBF solution. Ionic release from both BG, especially calcium and phosphorus ions in SBF solution and Dulbecco’s Modified Eagle Medium (DMEM) based on the inductively coupled plasma – optical emission spectrometer showed that HCA formation occurred on both BG surfaces, which corresponded to the increasing pH within 240 minutes incubation. Exposure of dental pulp stem cells (DPSC) to lower BG powder to liquid ratio (1 – 2 mg/ml) for both BG-conditioned media showed higher cell viability in Alamar Blue assay and higher cell proliferation in methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay, highlighting biocompatibility towards DPSC. DPSC exposed to lower BG powder to liquid ratio (1 – 2 mg/ml) for both BG 45S5 and 44S without an osteogenic inductive agent showed osteoinduction properties based on MTT, alkaline phosphatase activity, and total DNA assays. DPSC exposed to medium containing osteogenic inductive agent showed greater mineralisation based on von Kossa and Alizarin red staining. The 45S5 and 44S BG-conditioned media promoted osteogenic properties of DPSC. In conclusion, BG 45S5 and 44S were successfully fabricated and biocompatible towards DPSC, thus enhancing its viability, proliferation, and osteogenic differentiation. Hence, these bioactive glasses showed potential for application in regenerative dentistry.